Using Burke's Dramatistic Pentad to Interpret Chinese "Gao-Kao" High Stakes Testing and Stressing - Paralelled Testing in the U.S. as Cross-Cultural Context - Jim Schnell; Xiaoting Huang; Lei Wang (KOME: An International Journal of Pure Communication Inquiry, 2013)
The Chinese College Entrance Examination (“Gao-Kao”) is the mosthigh stakes assessment in China and parallels the most competitive examinations globally. Although it can provide Chinese educators and policy makers with an enormous pool of information about student achievement growth, school efficiency, etc., the current use of the test is mainly limited to ranking students by their raw scores. In this study, we tried two modifications to the traditional test toconnect the assessment outcomes with school accountability. First, we linked the Gao-Kao English tests from 2010 and 2011 and aligned them on a Rasch scale. Secondly, we collected background information of the examinees via a background survey.The result showed that students from Hainan province improved a little in 2011 overall. In addition, school level reports were generated to show the school’s growth as well as the county and province averages. By implementing test equating and background survey measures, this study demonstrated that Gao-Kao data can be used to construct a longitudinal data source as an initial step to build a value-added school accountability system.The aforementioned findings and how they are communicated help to frame global use of such high stakes testing. Kenneth Burke’s Dramatistic Pentad is used as foundation for communicative interpretation of these findings. The international context provides backdrop within which the findings are nested. Contrast with testing in the U.S. serves to highlight unique features of the Gao-Kao examination approach.